Exploring the impact of elevated pH and short maceration on the deterioration of red wines: physical and chemical perspectives - Carlos Artur Nascimento Alves; Aline Camarão Telles Camarão Telles Biasoto; Grace da Silva Nunes; Hélio Oliveira do Nascimento; Ronaldo Ferreira do Nascimento; Inglides Gomes Oliveira; Patrícia Coelho de Souza Leão; Lucicléia Barros de Vasconcelos (OENO One)
This study explored the impact of high pH and short maceration on red wines' physical and chemical traits and stability. Specifically, wines from Petit verdot, Merlot, Malbec and Tempranillo grapes, harvested in a tropical wine-producing region, were analysed. A consistent maceration period of 96 hours was applied in all vinification trials. After six months of bottling, parameters such as colour, acetaldehyde levels, higher alcohols and phenolic compounds were assessed. The findings highlighted significant impacts of grape pH on chemical stability, influenced by the phenolic profile of each grape variety. The short maceration period reduced phenolic compound extraction in high-pH musts, leading to decreased antioxidant potential and chemical stability. Critical indicators included colorimetric parameters, acetaldehyde and free SO₂ content. Acetaldehyde levels were strongly correlated with free SO₂ consumption and colour variations, signifying oxidative processes. Wines with higher concentrations of (+)-catechin, procyanidins and monomeric anthocyanins exhibited enhanced stability, while the presence of hydroxycinnamic acids was associated with oxidative changes. Caffeic acid emerged as a potential marker of oxidative stress, particularly in grapes from warmer climates. To improve the stability of wines made from high-pH grapes, extended maceration times or increased SO₂ dosages may be required.